An Empirical Study Of Human Resource Practices On The Performance Development Of Software Employees With Reference To IT Industries, Hyderabad. - Jayalakshmi, J.; Geeta, M. (Journal of Namibian Studies)
Hyderabad has become an important center for software development thanks to the rapid expansion and evolution of the IT sector. Competitiveness in an everchanging environment relies heavily on investing in the professional growth of software industry workers. The purpose of this empirical research is to examine how human resource practices in the setting of IT firms in Hyderabad affect the growth of software workers' performance. The study uses a mixed-method approach, using surveys, interviews, and secondary data analysis to look at how different HR policies affect the productivity of software workers. The research covers a wide range of HR-related topics, from hiring to employee development to performance evaluation to perks to work-life balance. The study's results highlight the role of HR policies and procedures in defining the professional growth of software workers. It stresses the significance of tailoring HR policies to the unique requirements of the IT sector and the circumstances in Hyderabad. Examining the connection between HR activities and software worker productivity, the study delves into the function that HR practices play in raising employee enthusiasm, contentment on the job, and output. The study also sheds light on the possibilities and obstacles encountered by IT firms in Hyderabad on their quest to optimize HR processes for performance improvement. For stakeholders in the IT business, HR experts, and politicians interested in creating a hospitable environment for software employees to flourish, this report provides significant insights and actionable recommendations. The findings of this study provide important insight into how to achieve long-term excellence in the IT industry by illuminating the complex relationship between HR practices and the performance development of software employees within the broader context of the Hyderabad tech hub.